Assessment of peri- and postoperative complications and Karnofsky-performance status in head and neck cancer patients after radiation or chemoradiation that underwent surgery with regional or free-flap reconstruction for salvage, palliation, or to improve function - Sertel Serkan; Bergmann Zazie; Lindel Katja; Münter Marc W; Federspil Philippe A; Bulut Cem; Simon Christian; Leitzbach Sarah; Plinkert Peter K (Radiation Oncology, 2011)
Abstract Background Surgery after (chemo)radiation (RCTX/RTX) is felt to be plagued with a high incidence of wound healing complications reported to be as high as 70%. The additional use of vascularized flaps may help to decrease this high rate of complications. Therefore, we examined within a retrospective single-institutional study the peri--and postoperative complications in patients who underwent surgery for salvage, palliation or functional rehabilitation after (chemo)radiation with regional and free flaps. As a second study end point the Karnofsky performance status (KPS) was determined preoperatively and 3 months postoperatively to assess the impact of such extensive procedures on the overall performance status of this heavily pretreated patient population. Findings 21 patients were treated between 2005 and 2010 in a single institution (17 male, 4 female) for salvage (10/21), palliation (4/21), or functional rehabilitation (7/21). Overall 23 flaps were performed of which 8 were free flaps. Major recipient site complications were observed in only 4 pts. (19%) (1 postoperative haemorrhage, 1 partial flap loss, 2 fistulas) and major donor site complications in 1 pt (wound dehiscence). Also 2 minor donor site complications were observed. The overall complication rate was 33%. There was no free flap loss. Assessment of pre- and postoperative KPS revealed improvement in 13 out of 21 patients (62%). A decline of KPS was noted in only one patient. Conclusions We conclude that within this (chemo)radiated patient population surgical interventions for salvage, palliation or improve function can be safely performed once vascularised grafts are used.